Với các số thực dương \(a,\,b\) thỏa mãn \(a^2+b^2=6ab\), biểu thức \(\log_2(a+b)\) bằng
\(\dfrac{1}{2}\left(3+\log_2a+\log_2b\right)\) | |
\(\dfrac{1}{2}\left(1+\log_2a+\log_2b\right)\) | |
\(1+\dfrac{1}{2}\left(\log_2a+\log_2b\right)\) | |
\(2+\dfrac{1}{2}\left(\log_2a+\log_2b\right)\) |
Chọn phương án A.
Ta có \(a^2+b^2=6ab\Leftrightarrow a^2+2ab+b^2=8ab\)
hay \((a+b)^2=8ab\).
Khi đó, $$\begin{eqnarray*}&\log_2(a+b)^2&=\log_2(8ab)\\
\Leftrightarrow&2\log_2(a+b)&=\log_28+\log_2a+\log_2b\\
\Leftrightarrow&\log_2(a+b)&=\dfrac{1}{2}\left(3+\log_2a+\log_2b\right).
\end{eqnarray*}$$